Cardiovascular Disease. (11th November 2018) - Summapund, J; Grant, E; Dickson, V; Matlock, D; Chaudhry, S; Katz, S; Blaum, C; Dodson, J
Abstract: BACKGROUND: As the use of coronary revascularization for older adults with AMI increases, more patients are exposed to both the potential benefits and associated procedural risks. Older adults' perspectives on these interventions, and their decisional needs, have been largely unexplored. We therefore conducted a qualitative study to: (1) understand patients' perspectives on interventional procedures, and (2) identify factors contributing to patients' decisions on whether or not to undergo revascularization. METHODS: In-depth, semi-structured interviews were conducted among 15 older adults (age ≥70 years) hospitalized with AMI at our center. All interviews were audio-recorded, transcribed verbatim, and coded using the ATLAS.ti qualitative software. Thematic analyses were conducted using an iterative team-based process. RESULTS: Four major themes emerged: (1) participants desire and value what they perceive to be shared decision making (SDM); (2) the most commonly perceived alternative to interventional procedures is death; (3) participants think minimally of procedural risks when compared with the perceived benefit; (4) participants place a high level of trust in treating clinicians when making decisions. Despite most participants stating they "had no choice" but to undergo the intervention (n=9), all found it very important to participate in SDM. Other factors, such as prior experience of an intervention or previous professions in medicine, also contribute to their decision-making process. CONCLUSION: While older adults hospitalized with AMI perceive coronary revascularization as a necessary life-saving procedure, patients still desire SDM. This study emphasizes the importance of presenting treatment options and strategies to effectively implement SDM in the setting of AMI.